Voltage-gated sodium channel expression and potentiation of human breast cancer metastasis - (:unkn) unknown (AMER ASSOC CANCER RESEARCH, 2005)
Purpose: Ion channel activity is involved in several basic cellular behaviors that are integral to metastasis (e.g., proliferation, motility, secretion, and invasion), although their contribution to cancer progression has largely been ignored. The purpose of this study was to investigate voltage-gated Na(+) channel (VGSC) expression and its possible role in human breast cancer. Experimental Design: Functional VGSC expression was investigated in human breast cancer cell lines by patch clamp recording. The contribution of VGSC activity to directional motility, endocytosis, and invasion was evaluated by in vitro assays. Subsequent identification of the VGSC alpha-subunit(s) expressed in vitro was achieved using reverse transcription-PCR, immunocytochemistry, and Western blot techniques and used to investigate VGSC alpha expression and its association with metastasis in vivo. Results: VGSC expression was significantly up-regulated in metastatic human breast cancer cells and tissues, and VGSC activity potentiated cellular directional motility, endocytosis, and invasion. Reverse transcription-PCR revealed that Na(v)1.5, in its newly identified neonatal splice form, was specifically associated with strong metastatic potential in vitro and breast cancer progression in vivo. An antibody specific for this form confirmed up-regulation of neonatal Na(v)1.5 protein in breast cancer cells and tissues. Furthermore, a strong correlation was found between neonatal Na(v)1.5 expression and clinically assessed lymph node metastasis. Conclusions: Up-regulation of neonatal Nav1.5 occurs as an integral part of the metastatic process in human breast cancer and could serve both as a novel marker of the metastatic phenotype and a therapeutic target.
Keywords: RAT PROSTATE-CANCER; GROWTH-FACTOR; NA+ CHANNELS; CELL-LINES; GENE-EXPRESSION; BETA-SUBUNITS; K+ CURRENTS; TENASCIN-R; IN-VITRO; RNA